DAMPAK DIGITAL MARKETING, BRAND IMAGE DAN RELATIONSHIP MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN LINA MS GLOW KOTA BENGKULU - Onsardi, Onsardi; Ekowati, Sri; Yulinda, Ade Tiara; Megawati, Megawati (Creative Research Management Journal, 2022)
The purpose of the study is to determine the influence of digital marketing, brand image and relationship marketing on purchasing decisions. This study is a survey study using quantitative methods. Population in this study is the entire Lena MS Glow store composition in Bengkulu city. The number of samples set was 190 with the accedental sampling technique. To collect research data using questionnaires, and data analysis techniques using path analysis with PLS SEM. The results of this study prove that digital marketing has a positive and significant influence on purchasing decisions. Brand image has a positive an significant influence on purchasing decisions. Relationship marketing has a positive and significant influence on purchasing decisions. This research is limited to the Lena MS Glow store custamers in Bengkulu city, with variables of digital marketing, brand image and relationship marketing and purchasing decisions. The results of the study contributed to the Lena MS Glow store as a reference to increase sales volume.